2017
DOI: 10.2174/1874306401711010010
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour Hypoxia and Pulmonary Hypertension in Patients with Idiopathic Pulmonary Fibrosis

Abstract: Background:The quantification of hypoxia based on resting partial pressure of arterial oxygen (PaO2) may underestimate hypoxia related to activities of daily living or sleep and thus not accurately reflect pulmonary hypertension (PH). The aim of the present study was to investigate the association of resting PaO2 with percent time of SpO2 below 90% (T90) and 88% (T88) in 24 hours. We also evaluated the capacity of hypoxia measures to predict PH in patients with idiopathic pulmonary fibrosis (IPF).Method:This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Use of 24‐h oximetry has been reported in adults with chronic lung disease and also in adults with obstructive sleep apnoea (OSA) . The purpose of these studies has been to look for hypoxic episodes during the day in adults with known OSA or pulmonary compromise.…”
mentioning
confidence: 99%
“…Use of 24‐h oximetry has been reported in adults with chronic lung disease and also in adults with obstructive sleep apnoea (OSA) . The purpose of these studies has been to look for hypoxic episodes during the day in adults with known OSA or pulmonary compromise.…”
mentioning
confidence: 99%
“…Of the 11 patients with normal VO 2 , only three (27.3%) had RV dysfunction (p = 0.38). Rodrigues et al [16] observed that patients with partial pressures of arterial oxygen (PaO 2 ) >70 mmHg at rest may experience severe hypoxemia (SpO 2 <90%) for a mean of >4 h per day, which would support the periodic occurrence of PH during the day. In agreement with this explanation, a marked increase in mPAP during exercise, which was frequently associated with a concomitant decline in SpO 2 , was observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with patients in very advanced IPF stages, patients with mild or moderate IPF may have variable pressure loads because of their broad spectrum of daily life activities. Different daily activity profiles may influence the pressure load due to transient hypoxemia, which is notably variable in IPF patients over a 24-h period [16] or due to differential pressure changes during exercise. In addition, the presence of tissue mediators [17] may contribute to premature PH in IPF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with patients in very advanced IPF stages, patients with mild or moderate IPF may have variable pressure loads because of their broad spectrum of daily life activities. Different daily activity profiles may influence the pressure load due to transient hypoxemia, which is notably variable in IPF patients over a 24-h period [16] or due to differential pressure changes during exercise. In addition, the presence of tissue mediators [17] may contribute to premature PH in IPF patients.…”
Section: Introductionmentioning
confidence: 99%